Tools for Rational Development: The Canada Land Inventory and the Canada Geographic Information System in Mid-twentieth century Canada - Stunden Bower, Shannon (Scientia Canadensis, 2018)
From the 1960s through the 1980s, Canadian scientists, resource managers, and computer experts collaborated on two linked undertakings: the Canada Land Inventory (CLI) and the Canada Geographic Information System. CLI was an extensive project that assessed the state of key resources across much of the country, while CGIS was a pioneering effort at computerizing CLI data to support decision-making about resource use. Fundamental components of the Agricultural Rehabilitation and Development Act, CLI and CGIS reflect Canadian innovation in new information-management tools designed to facilitate state goals. This paper examines the production and affordances of CLI and CGIS, and considers the renewed optimism and collaborative relationships that emerged from them. It also examines historical concerns over the limitations of these technologies and explores how CLI and CGIS were oriented to change over space, not time. Ultimately, these technological innovations served to naturalize patterns of inequality and normalize urban-industrial modernity.